Samarium and yttrium doping induced phase transitions and their effects on the structural, optical and electrical properties of Nd2Sn2O7 ceramics - YUMUŞAK, GÖRKEM (IOP PUBLISHING LTD, 2020)
In this work, the effects of Sm+3 and Y+3 doping onto the structural, optical and electrical properties of Nd2Sn2O7 are investigated. An atomic content of 3.49% and 4.29% of Sm and Y, respectively, were sufficient to alter the physical properties of the Nd2Sn2O7. Particularly, the Y+3 ionic substitution decreased the lattice constant, narrows the energy band gap, changed the conductivity type from n- to p- type and increased the electrical conductivity by 73 times without changing the cubic nature of structure of the pyrochlore ceramics. On the other hand, Sm+3 ionic substitutions changed the cubic structure to hexagonal or trigonal and forced optical transitions in the infrared range of light. The energy band gap shrunk from 3.40 to 1.40 eV, the defect density is reduced and the electrical conductivity increased by 47 times via Sm doping. These doping agents' makes the neodymium stannate pyrochlore ceramics more appropriates for optoelectronic applications.
Keywords: neodymium stannate; rare earth doping; lattice parameters; band gap; conductivity; PYROCHLORE OXIDES